Farmers' subjective valuation of subsistence crops: the case of traditional maize in Mexico - Aslıhan Arslan; J. Edward Taylor (Kiel Institute for the World Economy (IfW), 2008)
Shadow prices guide farmers' resource allocations, but for subsistence farmers growing traditional crops, shadow prices may bear little relationship with market prices. We econometrically estimate shadow prices of maize using data from a nationally representative survey of rural households in Mexico. Shadow prices are significantly higher than the market price for traditional but not improved maize varieties. They are particularly high in the indigenous areas of southern and southeastern Mexico, indicating large de facto incentives to maintain traditional maize there.
Keywords: O12; O13; Q12; Q39; 330; Shadow prices; non-market values; supply response; traditional crops; onfarm conservation; Mexico; Maisanbau; Subsistenzwirtschaft; Mais; Schattenpreis; Naturschutz; Mexiko